LIBIDIBIA FERREA: A COMPREHENSIVE REVIEW AND POTENTIAL APPLICATIONS OF DIFFERENT EXTRACTS OF JUCÁ (REMUNOM, 2026)
Secondary metabolites obtained from plants used in folk medicine have become a highly relevant field of research in the scientific community, due to their safety compared to synthetic substances that cause side effects. Among the plants used for this purpose is Libidibia ferrea, a plant rich in secondary metabolites such as gallic and ellagic acids, and also with a high protein content. In this sense, the present review aims to identify gaps in information regarding the plant parts explored, research institutions, the type of solvent used to obtain metabolites, and applications of the extract in technological invention processes. To this end, a systematic search process was carried out to select only manuscripts involving the obtaining of polyphenolic extract from Libidibia ferrea. It was observed that, among 44 selected manuscripts, in 33 of them, the fruits were the most explored for obtaining polyphenolic extract. Different solvents were combined with different parts of the plant to obtain the extract. Data from technological inventions have demonstrated that polyphenolic extracts have been applied in various products, including food and health products. The extensive compiled literature allows for the selection of which plant parts have potential for exploitation, as well as their applications